INFORMATION LITERACY IN THE DIGITAL ENVIRONMENT, SELF EFFICACY, SERVANT LEADERSHIP ON MANAGERIAL PERFORMANCE: STRATEGIC ROLE OF MANAGEMENT ACCOUNTANTS AS MODERATED MODEL - Sugiyarti, Listya; Sudibyo, Yvonne Augustine (CV. Radja Publika, 2023)
This empirical research attempts to evaluate the hypothesized relationship between information literacy in the digital environment, self-efficacy, servant leadership, and managerial performance, as well as the moderating role of management accountants. This research was conducted by taking a sample of 116 senior managers / staff who have in accounting, finance, marketing and HRD / HCM in Jabodetabek, Indonesia, by distributing questionnaires using Google Form and randomly some managers are visited to fill out statements in the questionnaire sheet. Data analysis techniques using SEM PLS version 3. Results from the tests indicate that there is a positive correlation between managerial performance and information literacy in the digital environment, between self-efficacy and managerial performance, between servant leadership and managerial performance and a negative correlation, between self-efficacy and the moderating effect of management accountants, and between servant leadership and managerial performance and a lack of moderating effect of management accountants. Keywords: Information Literacy, Digital Environment, Self Efficacy, Servant Leadership, Managerial Performance, Role of Management Accountants